Safety of Intravitreal Injection Guide. (January 2018) - Watanabe, Kei; Masafumi, Uematsu; Mohamed, Yasser H.; Watanabe, Takehito; Doi, Yusuke; Azusa, Fujikawa; Kitaoka, Takashi
Purpose: To evaluate the safety of our developed intravitreal injection guide. Methods: Retrospective review of all case notes for consecutive patients treated with intravitreal anti-vascular endothelial growth factor (VEGF) injections at the Department of Ophthalmology, Nagasaki University Hospital in Japan between January 2013 and December 2014. We included all patients who had at least 1 intravitreal anti-VEGF injection done within the study period. Data collected included demographics, indications of intravitreal anti-VEGF injections, type of injected drug, usage of intravitreal guide, experience of physicians, and any complication that occurred during or after the procedure. Results: The study included 256 patients (154 males and 102 females) who underwent 992 intravitreal anti-VEGF injections from January 2013 until December 2014. The mean age of the patients was 70.8 ± 11.3 years. Of total injections, 907 (91.44%) were done using the intravitreal guide, 60 (6.04%) were done without using the guide, and only 25 (2.52%) injections were not determined. Local complications include 1 (0.1%) case uveitis, 1 (0.1%) case retinal tear, and 1 (0.1%) case amaurosis fugax. There were no major complications as cataract, retinal detachment, and endophthamitis. No systemic complication was encountered. All complications occurred in the guide group without statistically significant difference in comparison to without guide group ( P = 1.0). All complications were related to experienced group without significant difference in comparison to limited experienced group ( P = .28). Conclusion: We conclude that the process of intravitreal injection with our developed intravitreal injection guide is safe and easy even for limited experienced physicians.